ESTIMASI CADANGAN KARBON PADA LAHAN KELAPA SAWIT MANDIRI DI KABUPATEN BARITO KUALA - Aminuddin Aminuddin; Yudi Firmanul Arifin; Gt. Syeransyah Rudy (Universitas Lambung Mangkurat, 2026)
Carbon is a natural element that has the symbol “C” with an atomic value of 12. More than half of the carbon bound by trees is transported underground, where it powers complex underground food networks and contributes to the formation of soil organic matter (SOM). Measuring and estimating carbon stocks in independent oil palm plantations requires a rigorous scientific approach, taking into account factors such as soil type, plant age and agricultural practices. Biomass is the total amount of aboveground living organic matter in a tree expressed as oven dry tons per unit area. Soil organic carbon (C-organic) is the main component of soil organic matter which has an important role in maintaining soil quality and supporting agricultural productivity. The objectives of this research are: (1) analyzing the amount of biomass on independent oil palm land; (2) analyzing carbon stocks on independent oil palm plantations; and (3) analyzing the organic C content in independent palm oil. This research carried out data collection from 8 plots on independent oil palm land in Barito Kuala Regency, using plots measuring 20 m x 60 m. This research used primary data and secondary data. Secondary data is carried out (1) managing and preparing tools and materials; (2) analyzing regional maps of independent oil palm plantations in Barito Kuala Regency; (3) biomass measurement; and (4) collecting and measuring biomass. Secondary data is obtained from various information from related agencies. The results of the research show that the biomass produced by palm oil with an age class of > 1.3 years is an average of 4.7 tons/m2 with a total biomass of 28.4 tons/m2, while the average amount of biomass produced by palm oil with this class is age < 1.3 years as much as from undergrowth on oil palm land with an average of 0.005 tonnes/m2 with a total biomass of 0.019 tonnes/m2. Carbon reserves produced from oil palm stands with an age class of > 1.3 years average 23.8 tons/ha with a total carbon reserve produced of 143.1 tons/ha. Carbon reserves produced from oil palm stands with an age class of <1.3 years average 0.20 tons/ha with a total carbon reserve produced of 0.75 tons/ha. Carbon reserves produced from undergrowth on oil palm land average 18.85 tons/ha with a total carbon produced of 150 tons/ha. The soil organic C content that has been carried out by research and laboratory testing has resulted in an organic C content in Plot 2 of 6.44%, in plot 3 of 2.59%, in plot 4 of 6.26% and in plot 7.42 %.